Aboriginal peoples - their struggle with cultural identity in the CARICOM region. - PALACIO, Joseph O. (1995)
Argues that the principal problem within the cultural identity of the region's aboriginal peoples does not come from themselves but from the dominant society which has not addressed how to define them and non-validates their cultural traits. Nonetheless, the aboriginal peoples have used various methods in the past and present to assert their identity.